Algogenic organic matter derived DBPs: Precursor characterization, formation, and future perspectives – A review. Issue 19 (2nd October 2019) - Hua, Lap-Cuong; Lai, Chun-Hsi; Wang, Gen-Shuh; Lin, Tsair-Fuh; Huang, Chihpin
Abstract: Algogenic organic matter (AOM) in water is a critical issue for sustainable treatment of drinking water, especially when algal eutrophication occurs because it is not amenable to removal by traditional coagulation/sedimentation/filtration processes. AOM is thus proved as a major precursor of disinfection by-products (DBPs). Its occurrence in water is undesirable and impacts the safety of drinking water. This review paper aims to broaden our current knowledge on the formation of AOM-derived DBPs and its precursor characterization. The future perspectives of research needs on AOM-DBP precursor characterization for an effective prediction are also given by this review. AOMs from various algal species have high-yielding potentials to produce both carbonaceous and nitrogenous DBPs upon chlorination, especially for the intracellular OM (IOM) from the algal cell. The practical treatment of eutrophic water with preoxidation thus should be used in caution to avoid the release of IOM from ruptured cells. Characterization of the physiochemical properties, such as basic parameters, optical properties, molecular weight distribution, and chemical functional groups, of AOM can give advantages for the better understanding of AOM-derived DBPs. Among the characterization tools, the fluorescent technique is highly recommended for the application of AOM-DBP prediction.